Iron triggers the early stages of cartilage degeneration in vitro: The role of articular chondrocytes. Issue 2 (June 2021) - Ferreira, A.V.; Duarte, T.L.; Marques, S.; Costa, P.; Neves, S.C.; dos Santos, T.; Granja, P.L.; Porto, G.
Abstract: Objective: Arthropathy is a major clinical problem in patients with hemochromatosis, the most common genetic disorder of iron overload. The pathological features of hemochromatosis arthropathy (HA) are heterogeneous and its specific nature remains unknown. One important drawback is the lack of proper in vitro models. The aim of the present study was to set up a model to investigate the biological response of cartilage to iron exposure. Design: Bovine articular cartilage explants were incubated with ferric citrate for up to 9 days. We evaluated chondrocyte viability, iron deposition, and biomarkers of cartilage degradation in the conditioned medium. Results: Iron accumulated within chondrocytes, which was associated with programmed cell death through chondroptosis. Iron treatment increased the release of sulfated glycosaminoglycans (sGAG), a component of the extracellular matrix, into the medium (p=0.0189). This was dependent on the presence of viable chondrocytes and was associated with increased activity of matrix-degrading metalloproteinases (MMP) (pro/active MMP-9, p=0.0317; pro MMP-2, p=0.0092; active MMP-2, p=0.0288). Co-treatment with the broad MMP/aggrecanase inhibitor prinomastat reduced iron-mediated sGAG release (0.02 ​μM, p=0.0425; 2 ​μM, p=0.0014), confirming that iron induces sGAG release via the activation of catabolic enzymes. Notably, iron-treated cartilage continued to release an increased amount of sGAG into the medium for 6 days after termination of the ferric citrate treatment (p=0.0259). Conclusions: Iron triggers the early stages of cartilage degeneration. Removal of iron exposure does not prevent further damage to the cartilage, thus providing a possible explanation why HA is not prevented after iron depletion by phlebotomy treatment.